On the specifi c features of attributive constructions in the texts of M. Tsvetaeva - Gubanov, Sergey A. (Известия Саратовского университета. Новая серия. Серия Филология: Журналистика, 2022)
The article deals with the description of the specifi c features of attributive constructions (epithet complexes) in M. Tsvetaeva’s texts. The Collected Works of the poet, as well as the Dictionary of Poetic Language served as the material for this research. The purpose of the research was to establish the structural and semantic idiostyle features of constructions containing words of attributive semantics in the poet’s texts. The research establishes that in the M. Tsvetaeva’s idiostyle, characteristic phrases and attributes occupy one of the leading places; some semantic groups of epithets (color, emotional evaluation and some others) and concepts defi ned by words refl ect the conceptual poetic picture of the world. In the process of analyzing the linguistic material, consistent patterns were revealed in the compatibility of epithets and defi ned objects. The conclusion has been drawn on the predominance of occasional forms of epithets of anthropomorphic semantics as part of attributive constructions. The paper proves that the structural and semantic features of attributive constructions revealed during the analysis refl ect in M. Tsvetaeva’s texts the specifi c features of the poet’s worldview, built on emotionality, particular expressiveness. Such confi gurations of epithet complexes built on repetitions of epithets, their mirror semantic refl ection, phonetic similarity, are a striking feature of M. Tsvetaeva’s texts. It is noted that the investigation of the epithet complex as a semantic unity of the epithet and the defi ned word (the object of epithetation) is an important stage in the study of the poet’s idiolect. The conclusion is made about the necessity for further linguistic analysis of the corpus of epithets and attributive constructions in the M. Tsvetaeva’s texts in order to provide a multidimensional description of the linguistic specifi city of poet's idiostyle, which will serve as an indispensable contribution to the epithet theory and the study of Tsvetaeva`s oeuvre.